Modelling plastic hinge of FRP-confined RC columns. (15th January 2017) - Yuan, Fang; Wu, Yu-Fei; Li, Chun-Qing
Highlights: Variation of plastic hinge length of RC columns under FRP confinement is studied. Plastic deformation zones and curvature concentration zone are quantified. Relation between jacket length and plastic hinge zones are studied and minimum jacket length is identified. Models for plastic hinge lengths are developed. Abstract: One of the key applications of Fiber Reinforced Polymer (FRP) in structural engineering is to provide confinement to the plastic hinge region of Reinforced Concrete (RC) columns. Due to the high complexity of the problem, current research on the behavior of RC plastic hinge is largely experimental; different and even contradicting models and conclusions have been reported. This gives rise to the need for more comprehensive studies of the problem that can only be done by numerical simulations due to the high cost of experiments. This paper provides a systematic investigation of the problem using three-dimensional finite element method (FEM). The FEM model is carefully calibrated with test results and an extensive sensitivity study is carried out to ensure the consistency of the results. An extensive parametric study of various affecting factors is carried out to study the problem and develop an improved model of the plastic hinge length. The accuracy of the model is verified with test data. It is found that both the lengths of the rebar yielding zone and the curvature localization zone increase first and then decrease as confinement increases, while the length of concrete crushing zone keeps decreasing with the increase in confinement. It is also found that the length of curvature localization zone should be considered as the physical plastic hinge length. A model of minimum jacketing length is developed for the first time, together with the improved plastic hinge length model, both of which can be conveniently used in engineering works.